2017
DOI: 10.1556/1886.2017.00025
|View full text |Cite
|
Sign up to set email alerts
|

Low neurotoxicity of ONX-0914 supports the idea of specific immunoproteasome inhibition as a side-effect-limiting, therapeutic strategy

Abstract: Application of the proteasome inhibitor Bortezomib for the treatment of haematopoietic malignancies such as multiple myeloma significantly improves the average overall survival of patients. However, one of the most severe side effects is the development of peripheral neuropathies caused by neurotoxic effects of Bortezomib limiting its therapeutic efficacy. With ONX-0914 a specific inhibitor of the β5i (LMP7)-immunosubunit containing proteasomes was developed that targets exclusively the proteasome subtypes mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…In comparison, ONX 0914 was much more cytotoxic than YU102. This result is consistent with previous studies showing near complete cell death in a primary neuron model after 48 hours treatment with 500 nM ONX 0914 73 . In addition, we found that LPS consistently sensitizes EOC-20 microglial cells to ONX 0914 but not to YU102 (Suppl.…”
Section: Resultssupporting
confidence: 93%
“…In comparison, ONX 0914 was much more cytotoxic than YU102. This result is consistent with previous studies showing near complete cell death in a primary neuron model after 48 hours treatment with 500 nM ONX 0914 73 . In addition, we found that LPS consistently sensitizes EOC-20 microglial cells to ONX 0914 but not to YU102 (Suppl.…”
Section: Resultssupporting
confidence: 93%
“…Studies in HeLa cells have elegantly shown that at concentrations of Bortezomib leading to 75% inhibition of chymotrypsin‐like activity, which effectively induces apoptosis in sensitive myeloma cells, only small inhibition of total protein breakdown is reached . Furthermore, the number of surviving primary neurons was strongly affected in the presence of Bortezomib, whereas ONX 0914 did not affect neuronal survival at concentrations up to 0.1 μmol/L, a concentration which depletes human monocyte subsets from PBMC cultures as demonstrated in this study. Hence, different sensitivities of cells toward (immuno)proteasome inhibition probably influence the side effect profile observed with these inhibitors.…”
Section: Discussionsupporting
confidence: 47%
“…Unlike constitutive β5 inhibitors, such as bortezomib and carfilzomib, it reduces the production of proinflammatory cytokines and cell-surface MHC Class I expression without apoptotic effects [142]. ONX0914 has shown efficacy in animal models of autoimmune disorders without affecting normal immune function [143,144]. Compared to ONX0914, KZR-616 has improved solubility and shows better efficacy in mouse models of antibody-induced arthritis [141].…”
Section: Kzr-616mentioning
confidence: 99%